ANALISIS PENGARUH FAKTOR MATERNAL DAN POLA ASUH TERHADAP PSIKOMOTORIK BAYI USIA 3-24 BULAN SEBAGAI SKRINING PENCEGAHAN STUNTING DI KABUPATEN BONE BOLANGO - Rita Amini Warastuti (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study intends to analyze the influence of maternal factors and parenting styles on the psychomotor of infants aged 3-24 months in preventing stunting. The test method with partial and simultaneous logistic regression to analyze maternal factors and parenting patterns consists of: Age at marriage, Knowledge of stunting, and Child's eating patterns, which are then associated with the infant's psychomotor. In 2021 and 2022, Ulantha Village will rank first as a Priority Village in preventing and overcoming stunting in Bone Bolango Regency. Although the stunting rate has decreased, it is not much different from previous years. These insignificant changes prompted research to analyze the influence of maternal factors and parenting styles on the psychomotor aspects of infants aged 3-24 months to determine the potential for stunting as a basis for making Regional Stunting Prevention Policies in Bone Bolango District. The results are based on partial logistic regression testing that the variables Age at marriage, Diet and Knowledge about stunting have a significant effect on children's psychomotor. Through simultaneous logistic regression analysis it is known that age at marriage, Knowledge about stunting and children's diet also has a significant effect on children's psychomotor skills. In conclusion, stunting prevention needs to be done as early as possible by screening children before the golden period ends, namely before the child is 2 years old, one of which is by monitoring the growth and development of children through the psychomotor abilities of children under 2 years of age, so it is hoped that stunting can be prevented and restored.